Enforceability Of International Humanitarian Law In Armed Conflict at Present (UUM Journal of Legal Studies, 2016)
The tendency of the current conflict is a new type of conflict, which is not regulated by international humanitarian law. After World War II, in any war, emphasize the protection of victims of war and an obligation to be responsible for violations of international law or international humanitarian law. The purpose this research is to explore the theories or the law resources in International Humanitarian Law to facing a new type of armed conflict.  It is also significant to know where the discovered principles international humanitarian law about the problem. Based on Martens Clause and 1977 Additional Protocol I and II or Si Omnes Clause and Common Articles 2 Geneva Conventions 1949 can applied in new type of armed conflicts. As the development of international humanitarian law which always follow the development of the international community, to address issues related to a new type of armed conflict, it can be back to the theories and legal resources in international humanitarian law.Keywords: Armed Conflict, International Humanitarian Law